Herb Archer interviewed by John Meredith for the John Meredith folklore collection - Archer, Herb, 1895-1987.; Meredith, John, 1920-2001. (1984)
Folkloric recording. Herb Archer sings folk songs and lilts dance tunes.
Recitation: 1. The wild colonial boy -- Singing : 2. The wild colonial boy -- Interview: 3. Stories of the naming of local creeks, 4. Dairying in the districts of Wollar, Bylong, Ulan, Mudgee, the story of his fiddle, 5. Describes first set of a dance -- Lilting: 6. First set tune, first fig, 2nd last fig, Lady's chain, 8. Varsoviana; Interview: 8. Varsoviana, 9. Schottische and Mick Pilley, 10. Schottische and Bob Thompson playing fiddle -- Lilting and interview: 11. Schottische, Ring the bell, 12 Waltz, Willie Digby, 13. Waltz, Starry night.
Recorded at Ulan, New South Wales on June 13, 1984.
Also available online
Timed summary (2 p.)
Keywords: Archer, Herb, -- 1895-1987 -- Interviews; Archer, Herb, -- 1895-1987 -- Performances; Folk dance music -- Australia; Folk songs, English -- Australia; Recitations